Bank Sampah : Solusi Meminimalisir Limbah Plastik di RW 10 Pekalipan - Syaeful Bakhri; Diana Putri (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
WASTE BANK: SOLUTION TO MINIMIZE PLASTIC WASTE IN RW 10 PEKALIPAN. The mentoring process in this community service program aims to observe the patterns of cooperation among community members in managing the waste bank and the utilization of the waste bank as an effort to minimize plastic waste through recycling activities at the Waste Bank of RW 10 Pekalipan, Kanoman Utara. Additionally, this program also seeks to assess the social and economic impacts of the waste bank's existence on the community. The mentoring conducted by IAIN Syekh Nurjati students with the residents of RW 10 Pekalipan revealed that the utilization of plastic waste through recycling at the waste bank has been running quite well. Plastic waste recycling activities at the RW 10 Waste Bank have brought significant benefits to the community and its members, including both social and economic advantages.The students acted as catalysts in the mentoring process, helping to optimize waste management practices to ensure they are efficient and economically valuable. This activity also provided education and awareness to the community about the importance of proper waste management, which contributes positively to the environment.